Case Report: Long-term disease-free survival in an advanced hepatocellular carcinoma patient: an exceptional response to PD-1 inhibitor therapy - Fang, Qinliang; Yu, Shuqi; Xiong, Yu; Zhang, Yibin; Wang, Xiaomin; Zhou, Jianyin; Wang, Fuqiang; Yin, Zhenyu (Frontiers in Immunology, 2025)
IntroductionHepatocellular carcinoma (HCC) is a leading cause of cancer-related death, with most patients diagnosed at advanced stages, often precluding surgical resection. Recently, immune checkpoint inhibitors, particularly PD-1 inhibitors, have emerged as promising therapies, though long-term disease-free survival (DFS) remains rare. We report a case of an advanced HCC patient who achieved complete remission (CR) after just four cycles of reduced-dose pembrolizumab and maintained a disease-free status for more than seven years.Case reportA 55-year-old male with chronic hepatitis B and alcohol-related liver disease presented with a ruptured HCC. After initial treatments, including surgery and chemotherapy, the patient was started on reduced-dose pembrolizumab (100 mg). After four cycles, the patient achieved CR.ConclusionThis case highlights the potential for long-term survival with reduced-dose PD-1 inhibitor therapy in advanced HCC. The patient’s exceptional response provides important insights into the role of personalized dosing, immune checkpoint inhibitors, and the management of immune-related adverse events.